Rare Missense Functional Variants at COL4A1 and COL4A2 in Sporadic Intracerebral Hemorrhage. (20th July 2021) - Chung, Jaeyoon; Hamilton, Graham; Kim, Minsup; Marini, Sandro; Montgomery, Bailey; Henry, Jonathan; Cho, Art E.; Brown, Devin L.; Worrall, Bradford B.; Meschia, James F.; Silliman, Scott L.; Selim, Magdy; et al.
Abstract : Objective: To test the genetic contribution of rare missense variants in COL4A1 and COL4A2 in which common variants are genetically associated with sporadic intracerebral hemorrhage (ICH), we performed rare variant analysis in multiple sequencing data for the risk for sporadic ICH. Methods: We performed sequencing across 559 Kbp at 13q34 including COL4A1 and COL4A2 among 2, 133 individuals (1, 055 ICH cases; 1, 078 controls) in United States–based and 1, 381 individuals (192 ICH cases; 1, 189 controls) from Scotland-based cohorts, followed by sequence annotation, functional impact prediction, genetic association testing, and in silico thermodynamic modeling. Results: We identified 107 rare nonsynonymous variants in sporadic ICH, of which 2 missense variants, rs138269346 (COL4A1 I110T ) and rs201716258 (COL4A2 H203L ), were predicted to be highly functional and occurred in multiple ICH cases but not in controls from the United States–based cohort. The minor allele of rs201716258 was also present in Scottish patients with ICH, and rs138269346 was observed in 2 ICH-free controls with a history of hypertension and myocardial infarction. Rs138269346 was nominally associated with nonlobar ICH risk ( p = 0.05), but not with lobar ICH ( p = 0.08), while associations between rs201716258 and ICH subtypes were nonsignificant ( p > 0.12). Both variants were considered pathogenic based on minor allele frequency (<0.00035 in European populations), predicted functional impact (deleterious or probably damaging), and in silico modeling studies (substantially altered physical length and thermal stability of collagen). Conclusions: We identified rare missense variants in COL4A1 / A2 in association with sporadic ICH. Our annotation and simulation studies suggest that these variants are highly functional and may represent targets for translational follow-up.